#EUROmicroMOOC: using Twitter to share trends in Microbiology worldwide. Issue 11 (20th June 2019) - López-Goñi, I; Giner-Lamia, J; Álvarez-Ordoñez, A; Benitez-Páez, Alfonso; Claessen, D; Cortesao, M; de Toro, M; García-Ruano, D; Granato, E T; Kovács, Á T; Romalde, J L; Sana, T G; et al.
ABSTRACT: Twitter is one of the most popular social media networks that, in recent years, has been increasingly used by researchers as a platform to share science and discuss ongoing work. Despite its popularity, Twitter is not commonly used as a medium to teach science. Here, we summarize the results of #EUROmicroMOOC: the first worldwide Microbiology Massive Open Online Course taught in English using Twitter. Content analytics indicated that more than 3 million users saw posts with the hashtag #EUROmicroMOOC, which resulted in over 42 million Twitter impressions worldwide. These analyses demonstrate that free Microbiology MOOCs shared on Twitter are valuable educational tools that reach broad audiences throughout the world. We also describe our experience teaching an entire Microbiology course using Twitter and provide recommendations when using social media to communicate science to a broad audience. Abstract : Trends in Microbiology by Twitter.